Pola Komunikasi Guru dan Siswa Yang Tidak Memiliki Gawai Dalam Pembelajaran di Masa Pandemi Covid-19 - May Prida Riani Rahmah (Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to determine the communication patterns used by teachers and students who do not have devices in learning during the covid-19 pandemic and the inhibiting factors encountered by teachers and students who do not have devices in learning during the Covid-19 pandemic. This study uses a qualitative research type. The technique of data collection was done by interview method. There were seven research informants consisting of four teachers and three students from SMP Negeri 3 Pancur Batu. Data analysis techniques are carried out starting from condensing data, displaying data and drawing conclusions and verification. The results of the study indicate that the communication pattern of teachers and students who do not have devices in learning during the covid-19 pandemic is using offline learning methods or learning communication that is carried out directly (face to face) which is arranged in a planned manner by each teacher in the field of study by providing a brief explanation. The materials taught then provide questions and exercises to students or make group discussions at school once a week or once every two weeks with a learning duration of two to three hours. The inhibiting factors for teachers and students who do not have devices in learning during the Covid-19 pandemic are the minimum duration of time for teachers to provide learning materials to students at school and the number of assignments or questions that make students less understand the material and cannot do the questions properly and correctly.